Comprehensive Review of Advances in Cosmetic and Restorative Dentistry - Almarwani, Manal Mohammed Eid; Adam, Emtenan Ahmed; Noffal, Amina Omar; Mohammedeid, Samiah Mohammed Noor; Bagadood, Muhmood Mohammed; Bahaider, Afnan Fowzy; Samara, Ahmad Adnan; Omran, Samia Mohammed; Moulana, Arjumand Abdulrahim; Sindi, Rehhaf Asaad; Alanozi, Wedad Khulaif Mohammed (Journal of Ecohumanism, 2024)
The work aims to present a systematic overview of cosmetic and restorative dentistry developments in the last three decades. Cosmetic and restorative dentistry is another advancement area that bears changes resulting from the material, technology, and technique improvements that are supportive and cosmetic improvement for patients. This review describes trends in dental restoration, tooth replacement, and esthetic procedures and the potential impact on improving patient care. Computer-controlled digital technologies, minimally invasive techniques, and biocompatible materials have become determinative for treatments and made processes less invasive and more easily predictable. The review also provides information about the future development in the given field and highlights that more innovations and challenges are coming.